Increasing the Stability of LiMn2O4 Against Harsh Conditions During Lithium Recovery from Real Brine Solutions - Hippauf, Felix; Abendroth, Thomas; Neidhardt, Julia; Althues, Holger; Aljlil, Saad A.; Alrasheed, Radwan A.; Alyousef, Yousef M.; Kaskel, Stefan (Energy Technology, 2021)
Brines are abundant waste products from desalination plants and have higher lithium contents than sea water (0.17 ppm). Herein, electrochemical lithium recovery from real brine solutions using Li-selective LiMn2O4 is reported. Free-standing electrodes are prepared completely solvent-free. At low current densities, the complete theoretical capacity of 148 mAh g−1 can be utilized. The process is highly rate dependent due to the lithium concentration in the mm range. The high salt content of the brine depicts a challenging environment for electrodes and reactor materials. Competing earth-alkali metals lead to scale formation blocking the electrode surface and reducing the electrode capacity for lithium uptake. The high chloride concentration enables the formation of chlorine Cl2 at potentials < 1 V versus Ag/AgCl competing with the deintercalation of lithium. A combination of commercial antiscalants was used to suppress the formation of CaCO3 at the electrode prolonging its cycle life. It is shown that a cation exchange membrane not only effectively blocks chloride ions from the electrode but also decreases the Li-diffusion. Finally, the selectivity of the process is proven in a real brine with a low lithium content (0.7 mm), and an actual recovery experiment is conducted in a flow setup.
CRIS-Team Scopus Importer:2022-04-14
Keywords: antiscalants; cation exchange membranes; electrosorption; lithium manganese oxide; lithium recovery